Disruption of ZC3H15 compromises telomere length maintenance by entrapping telomerase within cajal bodies - Chuanle Wang; Wei Chen; Ruofei Li; Yue Yang; Jiali Wu; Yuyang Tian; Zibin He; Song Lin; Xining Wang; Jianxi Zhu; Wenbin Ma; Zhou Songyang; et al. (Cell & Bioscience)
Abstract Background Telomere homeostasis is pivotal in various biological processes including ontogeny, reproduction, physiological aging, and the onset of numerous diseases such as tumors. In human stem cells and approximately 85% of tumor cells, telomerase formed by TERT and TERC RNA complex is responsible for elongating telomeres. However, the intricate and precise regulatory mechanisms governing telomerase remain largely elusive. Methods and results We developed a genome-wide trimolecular fluorescence complementation (TriFC) screen to identify TERC RNA-interacting proteins and found ZC3H15 (Zinc finger CCCH domain-containing protein 15) to interact with telomerase. ZC3H15 interacts with TERT via its N-terminal domain in an RNA-dependent manner. The proximity labeling technique PhastID revealed that ZC3H15 associates with proteins involved in regulation of ribonucleoprotein (RNP) complex biogenesis, snRNP assembly and RNA localization. Deletion of ZC3H15 upregulated telomerase activity but interestingly resulted in shortened telomeres and induced senescence in HTC75 cells, suggesting an unknown mechanism in regulating telomere length. Notably, we found ZC3H15 to associate with GEMs nuclear bodies, and its deletion led to the spatiotemporal fusion of GEMs and Cajal bodies, resulting in the sequestration of telomerase within Cajal bodies and a reduction in telomerase recruitment to telomeres during the S phase. Consistent with these findings, ZC3H15 ablation accumulated TERC precursor RNA. Conclusions These observations provide valuable insights into the molecular mechanisms by which ZC3H15 regulates telomerase dynamics and cellular senescence. ZC3H15 may represent a new target for cancer treatment and anti-aging therapies.